Learning Applied Fine Arts Materials Used by High School Students - Kurniawati, Novi; Sakre, Tantra (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This study aims to determine the stages of learning applied fine arts from used materials in grade XII-1 students of Kemala Bhayangkari 3 Porong High School. It is a qualitative descriptive research whose subjects are teachers and students of grade XII. Data collection techniques are carried out using observation, documentation, and interviews. The data analysis technique used is qualitative descriptive analysis. Based on the results of the research that has been carried out, it can be concluded that learning applied art from used towel materials goes through several stages, namely the learning planning stage, the learning implementation stage, and the learning assessment stage. Applied art can be used for human needs because it can be processed and made into crafts with use and beauty value. Applying art learning from used materials motivates students to develop creativity and learning skills. In the assessment, the weight of students' grades increased by 30% from the very low initial assessment in producing work, creativity, and innovation. The suggestions given include optimizing art infrastructure facilities in schools for hands-on practice. Learning should be focused on functional applied arts projects, and collaboration should be encouraged between students in groups.